A Study to Assess the Knowledge and Attitude of Prospective Parents Regarding Cord Blood Banking in Selected Areas of Vadodara - S. , Adithya; M Patel, Ekta; M. , Stuti Desai; Dindor, Pushpa; Diwan, Sumaiya; Jagat (International Journal of Psychosocial Rehabilitation, 2020)
Background: The concept of umbilical cord blood (UCB) stem cells is emerging as a non-invasive, efficacious alternative source of hematopoietic stem cells to treat a variety of blood and bone marrow diseases, blood cancers, metabolic disorders, and immune deficiencies. Aim: To assess the level of knowledge and attitude about cord blood banking among prospective parents. Material & Methods: The descriptive research design was adopted, and 100 samples were recruited by the nonprobability convenient sampling technique among prospective parents. The data was collected by a structured knowledge questionnaire and attitude scale. The collected data was optimized and analyzed by using descriptive and inferential statistics. Results: The study revealed that the majority of the subjects, 78 (78%), had inadequate knowledge, andts 22 (22%) had moderate knowledge on cord blood banking with a mean score of 6.3 and a standard deviation of 2.57. With regards to overall attitude, the majority of the subjects, 95 (95%), had a neutral attitude, and 5 (5 %) had a favorable attitude towards cord blood banking with a mean score of 66.04 and a standard deviation of 5.16. Conclusion: The present study concluded that nearly one-fourth of the participants had moderate knowledge and the majority of them had a neutral attitude about cord blood banking. Therefore, the healthcare workers have to initiate a strict awareness program regarding cord blood banking among prospective parents.